2003
DOI: 10.5326/0390311
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Integrity of Veterinary Surgical Gloves

Abstract: A multicenter, prospective study was performed to document the incidence of defective gloves postoperatively in veterinary surgery and to correlate defects with a variety of influencing factors. Gloves were collected after surgical procedures performed by the small animal clinical services at two veterinary teaching hospitals and one institution's student surgery laboratories. Gloves were evaluated for defects using electrical resistance testing. The overall incidence of glove defects was 23.3%. Significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 10 publications
5
27
1
Order By: Relevance
“…Interestingly, there was no difference in perforation rate between residents and faculty members acting as the primary surgeon. Character et al reported a higher rate of perforation in faculty members and suggested that more experienced surgeons are more aggressive, but this was not supported in our study. Individuals performing surgery did not accurately predict the presence or absence of glove defects, and in only 17% of procedures were they aware of a perforation.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, there was no difference in perforation rate between residents and faculty members acting as the primary surgeon. Character et al reported a higher rate of perforation in faculty members and suggested that more experienced surgeons are more aggressive, but this was not supported in our study. Individuals performing surgery did not accurately predict the presence or absence of glove defects, and in only 17% of procedures were they aware of a perforation.…”
Section: Discussioncontrasting
confidence: 93%
“…The overall incidence of postoperative glove perforations in our study was 18%. This is within the range of the incidence reported in other veterinary studies (10.2–26.2%) . These studies reported a similar increased risk for punctures in the nondominant hand, on gloves worn by the primary surgeon, and in surgeries of longer duration.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, glove punctures have been reported to occur in up to 34-43% of human surgical procedures [29-31]. In a study performed at two companion animal hospitals, glove punctures were found in one or both gloves in 148/382 (38.7%) glove pairs, and personnel were typically unable to predict whether or not a glove defect was present at the end of procedures [32]. Proper hand antisepsis prior to gloving for surgery therefore remains critical.…”
Section: Discussionmentioning
confidence: 99%
“…However, risk factors for other orthopedic instrumentation were not investigated. An additional veterinary study also identified orthopedic surgery as a risk factor for glove perforation and documented defects in 32% of procedures compared with 19% of soft tissue procedures …”
mentioning
confidence: 99%